Causes and forms of school bullying: A field study on students of Orouba Secondary School for Boys - Alsuwaidi, Sharifa (Al-Adab Journal, 2023)
The current study aims to identify the causes and forms of school bullying.To achieve the objectives of the current study, a non-probability sample was selected from the students of Al-Orouba School for Secondary Education, and the number of the sample members was (150) students, their ages ranged between (15-18 and above). To collect the necessary data for current study, a survey was designed to suit the objectives and purposes of the study. The results of the statistical analysis of the data of the current study showed the most common forms of bullying in school were (verbal - social - physical - sexual - electronic- bullying of property), It also showed the reasons of school bullying from the respondents’ point of view (personal reasons, family reasons, reasons related to the school environment, reasons related to the media and the technical revolution). The results of the study indicated the most common places in which bullying is practiced in the school and to the educational, psychological and social effects resulting from the phenomenon of school bullying. The study mentioned solutions from the respondents’ point of view to confront the phenomenon of school bullying.